The Preparation of Lactobacillus Probiotic as Enteric Coated Capsules for Diarrhea Patients - Rosainee Kha (Prince of Songkla University, 2016)
Thesis (M.Pharm., Pharmaceutical Sciences)--Prince of Songkla University, 2011